Pilkada dan Kewenangan Wakil Kepala Daerah Dalam Perspektif Hukum Tata Negara - Sudrajat, Hendra (Research and Development Agency Ministry of Home Affairs, 2020)
Since the reformation era in 1998 through amendments to the 1945 Constitution, which began in 1999 to 2002, it has impacted Indonesia's state administration system's structure. The direct election system's opening in the election of the President and Vice President and the legislature to the local leections (Pilkada). Local elections (Pilkada) candidates are a package for local leaders, which fascinating to examine. In Article 18, paragraph (4) to the 1945 Constitution does not mention the Deputy local leaders, thus causing problems. When the Deputy local leaders authority is limited by the constitution, which has an impact on conflicts of authority between the local leaders and Deputy local leaders, which results in disrupted government services. This study aims to provide a solution to this phenomenon so that it finds two options, namely, first to retain the position of Deputy local leaders in the local elections with the complaint mechanism method and precise judgment of taxation, and secondly to be consistent with the state constitution, the local elections (Pilkada) is held without a Deputy local leaders candidate with his position replaced. by the local secretary.